Effect of Diterpenes Isolated of the Marine Alga Canistrocarpus cervicornis against Some Toxic Effects of the Venom of the Bothrops jararaca Snake - Domingos, Thaisa; Vallim, Magui; Cavalcanti, Diana; Sanchez, Eládio; Teixeira, Valéria; Fuly, André (Molecules (Basel, Switzerland), 2015)
Snake venoms are composed of a complex mixture of active proteins and peptides which induce a wide range of toxic effects. Envenomation by Bothrops jararaca venom results in hemorrhage, edema, pain, tissue necrosis and hemolysis. In this work, the effect of a mixture of two secodolastane diterpenes (linearol/isolinearol), previously isolated from the Brazilian marine brown alga, Canistrocarpus cervicornis, was evaluated against some of the toxic effects induced by B. jararaca venom. The mixture of diterpenes was dissolved in dimethylsulfoxide and incubated with venom for 30 min at room temperature, and then several in vivo (hemorrhage, edema and lethality) and in vitro (hemolysis, plasma clotting and proteolysis) assays were performed. The diterpenes inhibited hemolysis, proteolysis and hemorrhage, but failed to inhibit clotting and edema induced by B. jararaca venom. Moreover, diterpenes partially protected mice from lethality caused by B. jararaca venom. The search for natural inhibitors of B. jararaca venom in C. cervicornis algae is a relevant subject, since seaweeds are a rich and powerful source of active molecules which are as yet but poorly explored. Our results suggest that these diterpenes have the potential to be used against Bothropic envenomation accidents or to improve traditional treatments for snake bites.